Different Fe(III) and Fe(II) complexes in clonal micropropagation of Gooseberry. Issue 1 (October 2020) - Nikulina, Elena; Akimova, Svetlana; Tsirulnikova, Nina; Kirkach, Vadim
Abstract: Iron chlorosis and tissue necrotization are often problems of plant growth in sterile conditions. Therefore, the overall multiplication factor and the productiveness dramatically decrease. The aim of work paper was to study the effect of various forms of iron chelates, including the stable complex of iron (II) with phosphorus-containing organic ligand, 1-hydroxyethylidenediphosphonic acid (HEDP), to the nutrient medium on the development of micro-shoots of Pink-2 (Rosovy-2) gooseberry cultivar according to Quoirin & Lepoivre (QL). Seven types of media were used in the screening: FeS04×7H20 + Na2EDTA (two control variant); Fe-EDTA - a complex of iron with ethylenediaminotetraacetic acid as such; Fe-DTPA (ferric diethylenetriaminepentaacetate), Fe3+ and Fe2+ -HEDP (ferric (III, II) 1-hydroxy ethylidene-1, 1-diphosphonate), Fe-EDDHA (ethylenediamine di-2-hydroxyphenyl acetate ferric). The influence of 4 concentration values of concentrations of introduced iron complexes were studied experimentally: reduced (×0.5), standard (×l), increased 1.5-fold (×l.5) and double concentration (×2). Results have shown that form of introduction of iron sources, the valence of the iron ion, the ligand types and their concentrations are important factors in shoot multiplication of gooseberry cultivar 'Pink-2'.